Rare Case of Pediatric Hypertrophic Obstructive Cardiomyopathy (HOCM) in A 6-year-old Boy: How to Recognize, Assess, and Manage the Risk? - Gabrielle Kartawan; Ria Ashriyah (Universitas Airlangga, 2023)
Highlights: It discusses pediatric HCM which is usually caused by autosomal dominant traits caused by mutation in cardiac sarcomere protein genes. It explains how to recognize the cardiac risk Abstract: Hypertrophic Obstructive Cardiomyopathy (HOCM) is a disease characterized by increased left ventricular (LV) wall thickness and accompanied by obstructive physiology measured by increased LV outflow tract gradient. It is mainly inherited in autosomal dominant traits caused by a mutation in cardiac sarcomere protein genes. In pediatrics, HOCM is rare and comprises a different diagnosis and management approach compared to adults. The risk of sudden cardiac death (SCD) is also higher in the pediatric population. Case Summary. This report is about a case of HOCM found incidentally in a 6-year-old boy and a discussion based on the latest literature review. The patient first came for evaluation for cardiac murmur and abnormality in ECG and chest x-ray. Diagnosis of HOCM was made through echocardiography assessment. Discussion. ICD implantation for primary prevention of SCD was considered based on individualized 5-year SCD risk assessment which is around 7%. Optimal pharmacological therapy with beta-blocker, careful planning of ICD implantation with balanced benefit and risk, and septal reduction surgery when indicated should extend the life expectancy and quality of life of pediatric HOCM. It is both essential and interesting to recognize pediatric HOCM diagnostic findings and to pursue further research about therapies of this rare disease.